International Arbitration as a department of resolution of international economic disputes - Shatalyuk, Artur (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
This article is dedicated to the problem of engaging arbitration as a transparent means of resolving disputes. Also at the present stage of reforms and changes in the sphere of international disputes, which, in their composition, have an economic direction, often arise the question of involving an arbitral tribunal as a prompt, transparent and competent body to meet the requirements of the conflicting parties. However, the question arises whether truly international arbitration is such an impeccable and competent body to whom it is possible to entrust its economic dispute to the interested parties. International commercial arbitration is by nature an arbitral tribunal. The mechanisms of its creation and functioning in the era of rapid integration processes, demonstrating the current economic situation, are a necessary and objective condition for ensuring legal regulation of the external economic and economic activity.International arbitration is one of the most effective and most open ways of solving economic (economic) disputes in the international arena. The activities of this body are regulated by the Law of Ukraine "On International Commercial Arbitration" of February 24, 1994, as well as taking into account all provisions on this arbitration, which are enshrined in international treaties of Ukraine. The international arbiter's reverse can suppress the following types of disputes:1.) disputes of civil law and contractual relations that canarise in the implementation of external trade or other typesInternational relations, if their enterpriseat least one of the parties is located outside the border;2.) disputes of various kinds between international organizations and associations and enterprises with international investments and between their participants, as well as disputes with other subjects of the law of Ukraine.Appeal to arbitration is voluntary, carried out by concluding by the parties of a special international agreement, which is called a compromise. On both sides regulate: the procedure for determining the composition of arbitrators; subject of dispute; the competence of arbitrage; procedure for consideration of the case; the nature and source of the norms on the basis of which the decision should be made; the order of making a decision; legal obligation of the decision.With regard to international arbitration awards, as well as a court decision of a particular country, must be enforced arbitrarily. In the case of international arbitration, this is provided for by various international treaties, which are obliged to ensure such enforcement.In view of the foregoing, one can conclude that consideration of economic disputes with an economic component of such an authority as international arbitration is and will be the most effective means of settling disputes in the international arena between stakeholders in international economic economic activity, which contains many indicators of such such as: speed, convenience, clarity, transparency, confidentiality, efficiency, as well as the possibility of implementing the decision of this body in the countries of the location of legal entities or their and other assets.